2006
DOI: 10.1007/s00040-005-0889-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for reproductive isolation between two colour morphs of cavity nesting honey bees (Apis) in south India

Abstract: In south India there are two distinct colour morphs of cavity nesting honey bees: the yellow Plain morph and the black Hill morph which are collectively known as Apis cerana. We show that the Hill morph is associated with a widely distributed mitochondrial haplotype that is present throughout mainland populations of south east Asian A. cerana. In contrast, the Plain morph, which is apparently confined to low to moderate elevations in India and Sri Lanka, is associated with a unique mitochondrial haplotype that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
(43 reference statements)
1
14
0
Order By: Relevance
“…The Plains cavity‐nesting bee from Kanataka groups with mainland A. cerana , although the two are genetically quite divergent: the value of 2.1% is similar to the distance (2.2%) between the examined representatives of A. cerana and A. nigrocincta (we note that four ‘Plain’ individuals from four different colonies were sequenced; in each case the sequences were identical for all three genes). This result is consistent with a previous study (Oldroyd et al, 2006) and supports the idea that the Plain Honey Bee represents a new species.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The Plains cavity‐nesting bee from Kanataka groups with mainland A. cerana , although the two are genetically quite divergent: the value of 2.1% is similar to the distance (2.2%) between the examined representatives of A. cerana and A. nigrocincta (we note that four ‘Plain’ individuals from four different colonies were sequenced; in each case the sequences were identical for all three genes). This result is consistent with a previous study (Oldroyd et al, 2006) and supports the idea that the Plain Honey Bee represents a new species.…”
Section: Resultssupporting
confidence: 93%
“…The second taxon of interest not included in the two recent molecular phylogenies is the yellow ‘Plains’ morph of cavity‐nesting honey bees from southern India. Based on a region that spans both coding and non‐coding regions between the tRNA leu and COII genes of the mitochondria, Oldroyd et al (2006) showed that the mitochondrial haplotype carried by this morphotype is dramatically diverged from the ubiquitous ‘mainland Asia’ family of haplotypes that are carried by other A. cerana (Fabricius, 1793) across its range (Smith & Hagen, 1996). In addition, drones of the ‘Plains’ morph have an earlier mating time than drones of the black ‘Hill’ morph, which is sympatric in south India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the differences in time of day between honey bee subspecies when drones perform mating flights are small (Drescher 1969;Tuchashvili 1969;Rowell et al 1986) and probably not important for the reproductive isolation. There are, however, differences in this respect between two colour morphs of A. cerana (Oldroyd et al 2006). In contrast to the prezygotic barriers mentioned above, there is no information about postzygotic barriers between honey bee subspecies-the hybrids, for example the Buckfast breading line, are both viable and fertile.…”
Section: Discussionmentioning
confidence: 96%
“…Mature Tropilaelaps mites, including the original female, emerge from the brood cell along with the hatching honey bee to search for new hosts. Tropilaelaps mites actively search for and enter a new honey bee brood cell within 1.3 days (Oldroyd et al, 2006).…”
Section: Biology Of Tropilaelapsmentioning
confidence: 99%